RARE-51. MOLECULAR INSIGHTS INTO MALIGNANT PROGRESSION OF CHOROID PLEXUS PAPILLOMA (CPP). (4th December 2020) - Yankelevich, Maxim; Finlay, Jonathan L; Gorsi, Hamza; Kupsky, William; Boue, Daniel R; Koschmann, Carl J; Kumar, Chandan; Mody, Rajen
Abstract: Malignant transformation of CPP is rare and the mechanisms remain elusive. We report a case of progression of papilloma into carcinoma where we performed molecular sequencing of both samples. A boy was found to have a brain mass soon after birth. The gross total resection (GTR) was diagnostic of CPP. Six years later he developed a recurrent mass that demonstrated progression to a choroid plexus carcinoma (CPC). The patient received chemotherapy according to a "HeadStartII" protocol. He is 2.5 years off therapy and disease-free. A sequencing study consisting of 1700 genes and tumor transcriptome was done. The analysis of both samples revealed a germline variant of TP53(R248W) with LOH and an allele frequency of 39% in the germline sample, suggesting a mosaicism. Analysis of both samples identified extensive aneuploidy and similar pattern of gains in chromosomes 7/8/12/20/21/X. Copy number aberrations newly acquired in the carcinoma included copy gain of chromosomes 5q/12/15q/20, and copy loss of chromosomes 5q/13/22. The papilloma was found to harbor 3 somatic mutations with 4% to 21% allelic fractions, all lost in the carcinoma. These mutations were of unknown significance and with too low allelic fractions to be responsible for the transformation. More pertinently, chromosomal aneuploidy was significant with additional losses in the carcinoma. This resulted in the losses of two critical tumor suppressor genes, RB and BRCA2, playing a possible role in the observed transformation. The "HeadStart" experience suggested that the prognosis of TP53 mutant CPC may be improved in the absence of radiation therapy.